Parodi Desain Kaos Kamengski Sebagai Gaya Hidup - Marsha Audra (AKSA: Jurnal Desain Komunikasi Visual, 2020)
T-shirts have become a timeless type of clothing. Over the years, tshirts have experienced development which is evidenced by thechanging of its form, design, and also function. Moreover, thesignificant increase in consumption level has been accompanied bythe growth in the needs of t-shirt production. With these increasedneeds, the t-shirt industry is becoming a competitive business for themanufacturers to produce a wide range of types and designs that cancaptivate consumers' interests. One of the strategies is by usingparody elements.One of the uses of parody designs that attracts attention isKamengski's work. Besides the success of bringing parody to each ofhis design works, Kamengski often received pros and cons. Apartfrom being able to identify the market gaps and being creative in theexisting limitations, the use of parody on Kamengski shirts design isconsidered as an act of plagiarism and deemed irresponsible.Beyond all of the pros and cons, the use of parody in t-shirtsdesigning can not be denied has become a part of the social lifestyle.This article will discuss the use of parody on t-shirt designs as alifestyle, with a case study of Kamengski t-shirts.